Colloidal titanium nitride nanobars for broadband inexpensive plasmonics and photochemistry from visible to mid-IR wavelengths. (15th December 2022) - Rej, Sourav; Santiago, Eva Yazmin; Baturina, Olga; Zhang, Yu; Burger, Sven; Kment, Stěpán; Govorov, Alexander O.; Naldoni, Alberto
Abstract: Developing colloidal plasmonic nanomaterials with high carrier density that show optical resonances and photochemical activity extending from the visible to the mid-infrared (MIR) ranges remains a challenging pursuit. Here, we report the fabrication of titanium nitride (TiN) nanobars obtained using a two–step procedure based on a wet chemical route synthesis of TiO2 nanowires and their subsequent high temperature annealing in ammonia flow. Electromagnetic simulations of the resulting TiN nanobars reveal a rich set of optical resonances featuring transverse, longitudinal and mixed transverse–longitudinal plasmonic modes that cover energies from the visible to MIR region. TiN nanobars decorated with Pt co-catalyst nanocrystals show enhanced photocatalytic hydrogen evolution activity in comparison to both isotropic TiN nanospheres of similar size and TiN nanocubes under near infrared excitation at 940 nm due to the enhanced hot electron generation. We also demonstrate that plasmonic TiN nanobars can be used for the detection of furfural molecular vibrations by providing a strong surface enhanced infrared absorption (SEIRA) effect in the MIR region. Graphical Abstract: ga1 Highlights: Titanium nitride (TiN) nanobars are synthesised using a nitridation process. TiN nanobars show plasmonic peak extending from visible to the mid-infrared range. TiN nanobars show higher hydrogen production rate over both nanospheres and nanocubes. Kinetic isotope effect and activation energy confirms hot electron role at 940 nm. TiN nanobars act as excellent substrates for surface enhanced infrared absorption spectroscopy.